2013
DOI: 10.1080/09084282.2013.778260
|View full text |Cite
|
Sign up to set email alerts
|

The Montreal Cognitive Assessment in Persons with Traumatic Brain Injury

Abstract: The objective of this study was to examine the performance of patients with traumatic brain injury (TBI) on the Montreal Cognitive Assessment (MoCA). The MoCA was administered to 214 patients with TBI during their acute care hospitalization in a Level 1 trauma center. The results showed that patients with severe TBI had lower scores on the MoCA compared with patients with mild and moderate TBI, F(2, 211) = 10.35, p = .0001. This difference was found for visuospatial/executive, attention, and orientation subtes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 37 publications
0
33
0
2
Order By: Relevance
“…45 Additionally, testing using the MoCA in other patient populations has not shown a sex difference. 23,24,30,46 In our study, an equal proportion of males (45%) and females (46%) had a history of one or more concussions, and males were not more likely to have three or more of SRC. When comparing male athletes only, no significant difference was found between contact/collision sports and no/limited contact sport athletes (26.4 ± 2.1 vs. 26.8 ± 2.1; p = 0.49), and a previous medical history of migraine, ADHD, anxiety, and depression did not influence the results.…”
Section: Sex Difference In Moca Scoresmentioning
confidence: 45%
See 1 more Smart Citation
“…45 Additionally, testing using the MoCA in other patient populations has not shown a sex difference. 23,24,30,46 In our study, an equal proportion of males (45%) and females (46%) had a history of one or more concussions, and males were not more likely to have three or more of SRC. When comparing male athletes only, no significant difference was found between contact/collision sports and no/limited contact sport athletes (26.4 ± 2.1 vs. 26.8 ± 2.1; p = 0.49), and a previous medical history of migraine, ADHD, anxiety, and depression did not influence the results.…”
Section: Sex Difference In Moca Scoresmentioning
confidence: 45%
“…21,[23][24][25][26][27][28][29] Most recently, three studies have administered the MoCA to patients with mild traumatic brain injury/concussion and found there was a relationship between severity of injury and lower scores on the MoCA. [30][31][32] The authors concluded that the MoCA was a useful cognitive screening tool for patients with mild to severe traumatic brain injury (TBI).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, either the English or the Spanish version was used. [10][11] The alternative versions were used twice across assessments (in the following order: 1, 2, 3, 1, 2, 3).…”
Section: Bloodmentioning
confidence: 99%
“…Subsequently, all epochs were averaged, and the mean of the power spectral density in different frequency bands were exported for statistical analysis. Frequency bands were chosen at target electrode sites based on previous literature pinpointing sites of maximal amplitude for each band: alpha(8)(9)(10)(11)(12)(13) at the occipital electrodes (O1, Oz, O2), theta (4-7 Hz) at the frontal electrodes (F7, F3, Fz, F4, F8), and delta (1-3 Hz) at the central electrodes (C3, Cz, C4). The averaged power spectral density extracted for each site (F, C, O) was expressed in absolute power (μV2) [22].…”
mentioning
confidence: 99%
“…Hasil penelitian ini sama dengan data dari salah satu rumah sakit di Jakarta, RS Cipto Mangunkusumo dimana kejadian cedera kepala tertinggi ialah cedera kepala ringan. 10 Hasil…”
Section: Bahasanunclassified